Czytelnictwo studentów w świetle badań empirycznych - Rogińska-Usowicz, Justyna (Biblioteka Uniwersytecka w Poznaniu, 2012)
Tematem artykułu są zainteresowania studentów, głównie czytelnicze, w świetle prowadzonych badań empirycznych. Materiał badawczy stanowią wyniki badań uzyskanych na podstawie ankiet i wywiadów przeprowadzonych od początku XX wieku po lata współczesne. Celem pracy jest uporządkowanie istniejącej literatury. W pierwszej części opisano ważniejsze badania prowadzone wśród studentów za granicą. Część druga artykułu poświęcona jest najważniejszym publikacjom krajowym.

The article discusses students interests, their readership profiles in particular, in view of available empirical studies documenting changes in readership habits. The research material consists of the results provided by studies conducted on the basis of surveys and interviews carried out among students since the beginning of the twentieth century to recent times. The article attempts to organize the existing literature. Part One provides a description of more important research studies carried out among students abroad. Part Two of the article focuses on the most important publications published in Poland.
Readership among students in view of empirical studies
Keywords: czytelnictwo; readership; studenci; students; podręczniki; textbooks; badania na temat młodzieży; youth surveys